Pengembangan Video Sex Education Untuk Menstimulasi Kemampuan Sosial Emosional Anak Usia Dini - Fitri, Norma Diana (Efektor, 2018)
This research aims to develop video sex education to stimulate social emosional of childhood. The development model used in this study is a model Borg and Gall (2007), which consists of ten steps. (1) Asses Needs To Identity Goal, (2) Conduct Instructional Analysis, (3) Analyze Learners And Cnontext, (4) Write Performance Objectives, (5) Develop Assessment Instrument, (6) Develop Instructional Strategy, (7) Develop And Select Instructional Materials, (8) Design And Conduct Formative Evaluation Of Instruction, (9) Revise Instruction, (10) Design And Conduct summative Evaluation. Design trials of investigational products through three stages: (a) validation expert, (b) small group trial, (c) a large group trial. The trial results were further tested by t-test is to determine the increase in the ability of religious values ​​and morals of the early childhood learning outcomes between consuming media by not wearing media. The results showed that audio-visual media can stimulate sex education religious values ​​and morals. From the analysis of the data obtained derive significant value 0.000 <0.005, H0 is rejected. Thus it can be said the difference in the average treatment before and after and the average score of the treatment before and after treatment in the learning process of sex education by using audio-visual media have been developed.